2D fluorescence spectroscopy for monitoring ion-exchange membrane based technologies – Reverse electrodialysis (RED). (1st January 2016) - Pawlowski, Sylwin; Galinha, Claudia F.; Crespo, João G.; Velizarov, Svetlozar
Abstract: Reverse electrodialysis (RED) is one of the emerging, membrane-based technologies for harvesting salinity gradient energy. In RED process, fouling is an undesirable operation constraint since it leads to a decrease of the obtainable net power density due to increasing stack electric resistance and pressure drop. Therefore, early fouling detection is one of the main challenges for successful RED technology implementation. In the present study, two-dimensional (2D) fluorescence spectroscopy was used, for the first time, as a tool for fouling monitoring in RED. Fluorescence excitation-emission matrices (EEMs) of ion-exchange membrane surfaces and of natural aqueous streams were acquired during one month of a RED stack operation. Fouling evolvement on the ion-exchange membrane surfaces was successfully followed by 2D fluorescence spectroscopy and quantified using principal components analysis (PCA). Additionally, the efficiency of cleaning strategy was assessed by measuring the membrane fluorescence emission intensity before and after cleaning. The anion-exchange membrane (AEM) surface in contact with river water showed to be significantly affected due to fouling by humic compounds, which were found to cross through the membrane from the lower salinity (river water) to higher salinity (sea water) stream. The results obtained show that the combined approach of using 2D fluorescence spectroscopy and PCA has a high potential for studying fouling development and membrane cleaning efficiency in ion exchange membrane processes. Graphical abstract: Highlights: Fouling deposition on ion-exchange membrane surfaces was monitored along time. Cation- and anion-exchange membranes were clearly distinguished by 2D fluorescence spectroscopy. 2D fluorescence spectroscopy combined with PCA was used, successfully, for RED process monitoring. Efficiency of membrane cleaning was evaluated. Humic acids transport from dilute to concentrated compartment was detected.